2013
DOI: 10.1161/circulationaha.113.002717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visit-to-Visit Variability in Systolic Blood Pressure on Macrovascular and Microvascular Complications in Patients With Type 2 Diabetes Mellitus

Abstract: A recent study of several cohorts of patients with previous transient ischemic attack or stroke and of the AngloScandinavian Cardiac Outcomes Trial Blood Pressure Lowering Arm (ASCOT-BPLA) reported that visit-to-visit Background-Recent evidence suggests that visit-to-visit variability in systolic blood pressure (SBP) and maximum SBP are predictors of cardiovascular disease. However, it remains uncertain whether these parameters predict the risks of macrovascular and microvascular complications in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
128
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 26 publications
20
128
4
Order By: Relevance
“…We showed an association between higher SD_SBP and higher risk of renal outcomes similar in magnitude to the association that has been seen for the association of SBP variability with CVD outcomes (6,7,10); the association persisted after multivariable adjustment for important potential confounders, including baseline eGFR and mean BP. An association also tended to be present for average real variability and peak value, two alternative measures of SBP variability.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We showed an association between higher SD_SBP and higher risk of renal outcomes similar in magnitude to the association that has been seen for the association of SBP variability with CVD outcomes (6,7,10); the association persisted after multivariable adjustment for important potential confounders, including baseline eGFR and mean BP. An association also tended to be present for average real variability and peak value, two alternative measures of SBP variability.…”
Section: Discussionsupporting
confidence: 81%
“…However, studies showing a higher risk for advanced renal disease, such as ESRD, have been restricted to persons with diabetes. An analysis of individuals participating in the Action in Diabetes and Vascular Disease: Preterax and Diamicron Controlled Evaluation (ADVANCE) Trial, all of whom had diabetes, found increasing risk for the combined end point of new macroalbuminuria (.300 mg albumin per 1 g creatinine), doubling of serum creatinine, need for RRT, or renal death with increasing decile of SBP variability (10). However, this analysis did not adjust for baseline renal function or albuminuria.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, diabetes was a modified factor based on our study. Consistent with the results from the Action in Diabetes and Vascular Disease (AD-VANCE) Trial, 23) which included 8811 patients, visit-to-visit variability of SBP clearly predicted the future development of major microvascular complications among patients with diabetes.…”
Section: Discussionsupporting
confidence: 77%
“…Using the SD of systolic BP measured over successive clinic visits, a common VVV metric, several groups have shown that greater VVV is associated with increased risk for cardiovascular events in patients with diabetic and nondiabetic CKD; the corresponding relation of VVV with renal events has largely been limited to diabetic individuals (6)(7)(8)(9). In this issue of the Clinical Journal of the American Society of Nephrology, Whittle et al (10) report the association of VVV with renal events in 21,245 participants from the Antihypertensive and LipidLowering Treatment to Prevent Heart Attack Trial (ALLHAT).…”
mentioning
confidence: 99%